OSTEOPOIKILOSIS: TWO CASE REPORTS - Mehmet Ali Taşkaynatan,; Bülent Hazneci,; Evren Yaşar,; Ahmet Özgül,; Tunç Alp Kalyon, (Archives of Rheumatology, 2005)
Osteopoikilosis is an uncommon osteosclerotic dysplasia. There is no exact evidence of its etiology and pathogenesis. Usually, it is an asymptomatic disease and the diagnosis is made incidentally from radiographs which show multiple, small, well-defined, variably shaped and widely distributed sclerotic areas over the skeleton. Herein we report two cases of osteopoikilosis admitted with low back pain complaints and discuss the atypical case versus typical case with literature.